Comparative Study of Physico-Chemical Parameters and Zooplankton Bio Diversity Between Twolakes (Pathipaka and Chinnakodepaka) at Jayashankar Bhupal Pally District - Veena, Polasani; Sridevi, Boddireddy; Swapna, Padidela (Journal of Neonatal Surgery, 2025)
Water is essential for living organisms especially like Flora and Fauna. The presented study deals with comparative study of the periodic and aperiodic variations of Physico-chemical status of two lakes belongs of Pathipaka Lake and chinnakodepakaLake of Bhupal pally Jayashnkar District,in Telangana. Both lakes having natural freshwater body. Different data are collected and observed through various field trips. A comparative study of the periodic and aperiodic variations of the Physico-chemical status of two lakes were studied in year 2023-2024. Both the lakes are biotically affected by various anthropogenic activities. In the present study water characteristics of two lakes have been compared the water quality. Different Parameters like Temperature, pH, conductivity, COD, BOD and also Zooplankton diversity. Both lakes are suitable for Fish culture and they are not polluted ponds